Production of small RNAs by mammalian Dicer - Svobodova, Eliska; Kubikova, Jana; Svoboda, Petr (Pflügers Archiv, 2016)
MicroRNA (miRNA) and RNA interference (RNAi) pathways employ RNase III Dicer for the biogenesis of small RNAs guiding post-transcriptional repression. Requirements for Dicer activity differ in the two pathways. The biogenesis of miRNAs requires a single Dicer cleavage of a short hairpin precursor to produce a small RNA with a precisely defined sequence, while small RNAs in RNAi come from a processive cleavage of a long double-stranded RNA (dsRNA) into a pool of small RNAs with different sequences. While Dicer is generally conserved among eukaryotes, its substrate recognition, cleavage, and biological roles differ. In Metazoa, a single Dicer can function as a universal factor for RNAi and miRNA pathways or as a factor adapted specifically for one of the pathways. In this review, we focus on the structure, function, and evolution of mammalian Dicer. We discuss key structural features of Dicer and other factors defining Dicer substrate repertoire and biological functions in mammals in comparison with invertebrate models. The key for adaptation of Dicer for miRNA or RNAi pathways is the N-terminal helicase, a dynamically evolving Dicer domain. Its functionality differs between mammals and invertebrates: the mammalian Dicer is well adapted to produce miRNAs while its ability to support RNAi is limited.
Keywords: Animals; molekulární evoluce; MicroRNAs; lidé; zvířata; Ribonuclease III; ribonukleasa III; Evolution, Molecular; mikro RNA; Humans